Diminutives in Classical and Colloquial Arabic (Comprehensive Journal of Science, 2026)
This study examines the phenomenon of diminutives as one of the prominent morphological and semantic features in the Arabic language. It aims to identify and analyze the similarities and differences between the diminutive system in Standard Arabic, as a regular and rule-governed system, and in contemporary colloquial Arabic, as a stylistic system based largely on usage.The research problem lies in how the standard diminutive rules are employed in everyday colloquial discourse, and how they undergo transformations that shift them from a generative morphological structure into fixed lexical patterns used for specific semantic purposes.The study adopts a descriptive contrastive approach, comparing the three diminutive patterns in Standard Arabic (fuʿayl, fuʿayʿil, fuʿayʿīl) with their corresponding forms in various dialectal environments.The study concludes with several key findings, including:Structural Level: Colloquial Arabic retains the basic diminutive structure but often drops the initial vowel (ḍamma), replacing it with a consonant cluster or a reduced form. Functional Level: The functions of diminutives in colloquial Arabic are reduced to expressing affection, smallness, and temporal or spatial proximity. Lexical Level: Many diminutive forms in colloquial Arabic have become lexicalized as fixed expressions (such as proper names and tool names), losing their original derivational connection.